A War Film Without War Images - Dumbadza, Soso (Germany, 2011)
Through extensive use of archival footage found on the ineternet and recorded off-air from television the documentary film analyzes the growing Georgian nationalism.
Donation from OSI-Budapest Arts and Culture Program.
Keywords: Documentary films